Autoimmune thyroiditis and vitiligo in a child with minimal change nephrotic syndrome - Kuzmanovska, D B; Shahpazova, E M; Kocova, M J; Gruevska, S J; Petrushevska, G (Springer Science and Business Media LLC, 2001)
We report a 12-year-old child with multiple autoimmune components consisting of minimal change nephrotic syndrome (MCNS), Hashimoto's thyroiditis and vitiligo. This boy presented with MCNS, complicated by acute renal failure, and subsequently developed Hashimoto's thyroiditis and vitiligo. Conventional prednisone treatment did not induce remission, but multiple high dose infusions of methylprednisolone led to remission. The occurrence of nephrotic syndrome, Hashimoto's thyroiditis and vitiligo suggests that similar immunological mechanisms may be involved in the pathogenesis of these diseases.